PROBLEM-PROBLEM KUNCI DALAM FILSAFAT BAHASA BIASA - Muhammad Hilal (LP3M IAI Al-Qolam Malang, 2020)
The Ordinary Language Philosophy has been a philosophical trend in England, especially, and around the world. This philosophical trend offered a methodology to think and make speculation philosophically in a correct and relevant way. That methodological offering is language analysis. Therefore, some key problems mentioned here are related to language, because language as conceived by Ordinary Language Philosophy is a window for knowing and understanding the world. This conception leads to the discussion on the limit of the world and theory of meaning. These discussion on both limit of the world and theory of meaning determines the conception of Ordinary Language Philosophy about the function and task of philosophy. Keywords: Ordinary Language Philosophy, task of philosophy, limit of the world, theory of meaning.